Analysis of The Influence of Taste, Packaging, Brand and Quality on Purchase Decisions For Conato Bakery Bread Products Jember - Bella, Mia Twu; Ambarkahi, Ratih Puspitorini Yekti; Dhamayanthi, Wenny (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
This research reveals the influence of consumer behavior in particular consumers at Conato Bakery regarding purchasing decisions namely by analyzing Influence Attribute Product Regarding Purchasing Decisions​ Conato Bakery Jember Bread Products. This research reveals the influence of taste factors, packaging, brand and quality product both simultaneously or partially, as well as regarding the factors that have a dominant influence on purchasing decisions Conato Bakery Jember bakery products. The analytical tool used in this research is multiple linear regression analysis. Overall, the results of this research can be concluded that variable taste, packaging, brand and quality product simultaneously have a significant influence on purchasing decisions product bread​ Conato Bakery Jember. Partially,​ taste and quality of the product influential significant impact on purchasing decisions for bread products Conato Bakery Jember, will but in research this time packaging and brand variables have no significant effect on decision purchase bakery products Conato Bakery Jember.